Mechanisms of acupuncture in treating depression: a review - Jianfu Ma; Xuan Yin; Kaiyu Cui; Jiqing Wang; Wei Li; Shifen Xu (Chinese Medicine)
Abstract Background Acupuncture as a representative treatment method of traditional Chinese medicine, has been found to have a significant effect on mild to moderate depression without obvious side effects, but the mechanism through which it exerts its antidepressant effect is still unclear. Methods We searched PubMed, Web of Science, and Embase databases for basic research on acupuncture in the treatment of depression from the database established to June 14, 2024, and finally included 44 studies from 2020 to June 14, 2024, into the table analysis. The main outcomes of this study are the effects of acupuncture on the relevant biological indicators of depression model. Results By analyzing the effect of acupuncture on rodent model of depression, the mechanism of acupuncture against depression was explored. In general, several acupuncture methods, mainly based on electroacupuncture (EA), regulate the levels of 5-hydroxytryptamine (5-HT), glutamic acid (Glu) and dopamine (DA), regulate the calcium signaling pathway, increase the expression of synaptic protein, promote mitochondrial repair and reduce oxidative stress, and enhance synaptic plasticity. Inhibition of key inflammatory pathways such as P2X7R/NLRP3 and NF-κB signaling pathways, regulation of hypothalamic–pituitary–adrenal axis (HPA axis) function, and tryptophan metabolism improved depression-like behavior in rodent models. Conclusions In summary, acupuncture treatment represented by EA has multiple mechanisms to play a role by regulating neurotransmitter balance, improving neuroplasticity, reducing inflammatory responses, and regulating the neuroendocrine system. However, the differences between acupoint catgut embedding (ACE), manual acupuncture (MA), and EA in the treatment of depression and the operating parameters of EA in the treatment of depression with different causes (such as frequency, intensity, duration, etc.) still need further research to be confirmed. This review has not been registered with PROSPERO or other protocol registration platforms because protocol registration was not a mandatory requirement for this study.